Indigenous higher education sector: the evolution of recognised Indigenous Leaders within Australian Universities. Issue 2 (8th December 2021) - Coates, Stacey Kim; Trudgett, Michelle; Page, Susan
Abstract: There is clear evidence that Indigenous education has changed considerably over time. Indigenous Australians' early experiences of 'colonialised education' included missionary schools, segregated and mixed public schooling, total exclusion and 'modified curriculum' specifically for Indigenous students which focused on teaching manual labour skills (as opposed to literacy and numeracy skills). The historical inequalities left a legacy of educational disparity between Indigenous and non-Indigenous Australians. Following activist movements in the 1960s, the Commonwealth Government initiated a number of reviews and forged new policy directions with the aim of achieving parity of participation and outcomes in higher education between Indigenous and non-Indigenous Australians. Further reviews in the 1980s through to the new millennium produced recommendations specifically calling for Indigenous Australians to be given equality of access to higher education; for Indigenous Australians to be employed in higher education settings; and to be included in decisions regarding higher education. This paper aims to examine the evolution of Indigenous leaders in higher education from the period when we entered the space through to now. In doing so, it will examine the key documents to explore how the landscape has changed over time, eventually leading to a number of formal reviews, culminating in the Universities Australia 2017–2020 Indigenous Strategy (Universities Australia, 2017).